Microbiome Methods in Experimental Autoimmune Encephalomyelitis. Issue 12 (6th December 2021) - Daberkow, David P.; Hoffman, Kristina; Kohl, Hannah M.; Long, Tyrel; Kirby, Trevor O.; Ochoa‐Repáraz, Javier
Abstract: Microbiome composition studies are increasingly shedding light on animal models of disease. This paper describes a protocol for analyzing the gut microbiome composition prior to and after the induction of mice to experimental autoimmune encephalomyelitis (EAE), the principal animal model of the human neuroinflammatory demyelinating disease multiple sclerosis (MS). We also address and provide data assessing the impact of mice reared in different animal facilities on EAE induction. Furthermore, we discuss potential regulators of the gut‐microbiome‐brain axis (GMBA) in relation to neuroinflammation and implications on demyelinating disease states. Our results suggest that mice reared in different animal facilities produce different levels of EAE induction. These results highlight the importance of accounting for consistent environmental conditions when inducing EAE and other animal models of disease. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Study of the composition of the gut microbiome in the neuroinflammatory model of experimental autoimmune encephalomyelitis Basic Protocol 2 : Experimental procedures for DNA extraction and microbiome analysis